"I Know They Meant Well…": Helpful and Hurtful Memorable Messages During Mourning. Issue 5 (4th July 2022) - DeGroot, Jocelyn M.; Carmack, Heather J.
Abstract: This study explores 112 helpful and hurtful memorable messages identified by the bereaved when receiving condolences after a loss. An online open-ended qualitative questionnaire revealed that the most frequently used hurtful memorable messages were comments that attempted to rationalize the death or remarks that minimized the loss in some way. The most helpful messages were the interactions that provided the bereaved space to grieve. Some categories of statements were evident in both helpful and hurtful messages, and so, caution should be exercised if making statements related to giving advice or exuding positivity.